Pathophysiology, prevention, and treatment of medication overuse headache. Issue 9 (September 2019) - Diener, Hans-Christoph; Dodick, David; Evers, Stefan; Holle, Dagny; Jensen, Rigmor Hoejland; Lipton, Richard B; Porreca, Frank; Silberstein, Stephen; Schwedt, Todd
Summary: Regular or frequent use of analgesics and acute antimigraine drugs can increase the frequency of headache, and induce the transition from episodic to chronic headache or medication overuse headache. The 1-year prevalence of this condition in the general population is between 1% and 2%. Medication overuse headache is more common in women and in people with comorbid depression, anxiety, and other chronic pain conditions. Treatment of medication overuse headache has three components. First, patients need education and counselling to reduce the intake of medication for acute headache attacks. Second, some patients benefit from drug withdrawal (discontinuation of the overused medication). Finally, preventive drug therapy and non-medical prevention might be necessary in patients at onset of treatment or in patients who do not respond to the first two steps. The optimal therapeutic approach requires validation in controlled trials.